The Impact of title sponsorship on customer-based brand equity: an evaluation of seasonal soccer tournaments in South Africa - Sibiya, Mxolisi (School of Management Studies, 2020)
Sports sponsorship has become an integral brand building tool as brands wrangle to be differentiated and to create loyal customers. Sponsorship is seen as impactful as it brings brands closer to consumers through a passion point and by borrowing equity of the sponsored property. As the sponsorship market continues to grow, brands are diversifying into title sponsorship of short-term tournaments to gain a competitive edge. The mere association by means of name sharing as title sponsors is not strong enough to alter what consumers see, hear, feel, and think of the brand. Thus, brands have to employ brand experiences that are engaging, enjoyable, and memorable enough to deliver lasting impact on consumers in terms of what consumers see, hear, feel, and think. These modules together form customer-based brand equity (CBBE), the potential commercial value that a brand can derive based on what resides in the mind of consumers. Nonetheless, there is currently no scholarly investigation that examines the impact that brand experiences has on CBBE. The goal of this research is to unpack the proliferation of title sponsorship in short-term tournaments and explore if CBBE is impacted by employing brand experiences during short-term tournaments. The thesis aims to establish an academic foundation to strengthen the interpretation of the relationship between sponsorship of short-term tournaments and the experiences used to impact CBBE. To achieve this objective, the study presents an adapted framework for interpretation as no scholarly model currently exists. The relationship interpretation is achieved through thorough investigation of existing literature that integrates short-term tournament title sponsorship, brand experiences, and CBBE. Furthermore, custodians of brands that title sponsor short-term tournaments were the focal population of the study to understand their strategic imperatives that inform the relationship under study as research reveals that more title sponsors are integrating brand experiences into their sponsorships.